Become Captain of Your Financial Ship: Evaluation Survey - Josephine Turner (EDIS)
FCS7225, a 1-page survey by Josephine Turner, provides a worksheet for evaluating the Become Captain of Your Financial Ship series and curriculum. Published by the UF Department of Family, Youth and Community Sciences, January 2007.